ANALISIS DAYA SAING SEKTOR INDUSTRI PRIORITAS INDONESIA DALAM MENGHADAPI PASAR ASEAN - Isventina Isventina; Nunung Nuryartono; Manuntun Parulian Hutagaol (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2015)
This study aimed to analyze the factors that influence competitiveness of Indonesia’s priority industrial sector in facing the ASEAN market by using Revealed Comparative Advantage (RCA) and panel data analysis. The study period was in 2001-2013 and variables are used, among others, the export price of products in the industry priorities, labor productivity, fixed capital and riil exchange rate. Based on the calculation of the level of competitiveness by using RCA, showed that the Indonesia's priority industrial sectors have strong competitive (RCA>1) in the ASEAN market, except for the chemical industry and machinery and equipment industry. That is, Indonesia has a comparative advantage in most of the priority industrial sectors, so that it can be used to support the government's strategy to expand the national industrial market to the ASEAN region. While the results of the panel data analysis showed that the export price is the most influential factor for the competitiveness of priority industrial sectors in Indonesia. In this case, the export price is a reflection of the production cost. The high of production cost indicates that the purchase price of inputs by exporting companies is also high, so that the export price was high. Because the essence of competitiveness is relatively low cost, the high export prices showed a decreasing competitiveness. Other factors that affect are the real exchange rate and labor productivity. Rupiah depreciation can encourage the growth of exports, which in turn can improve competitiveness. Meanwhile, the development of human resources that make industrial policy was originally based on cheap labor and natural resources can be developed into a productivity-based industries are supported by qualified human resources as well as science and high technology. On the other hand, the addition of variable fixed capital does not affect the competitiveness of priority industrial sectors. This is because the impact of the increased competitiveness of the addition of fixed capital in a given year is not directly felt in the year, but will be felt in the next few years. Thus, the strategy can be formulated to improve the competitiveness of the priority industrial sectors, including developing the upstream industry and among industry based on natural resources and the control of exports of raw materials, develop human resources industry players in the Indonesia’s priority industrial sectors with training and innovation activities, developing downstream industries as well as the increase in value-added products in the priority industrial sectors through product diversification and improve the pattern of cooperation with the manufacturers of other countries in the ASEAN region through the export promotion.  Keywords: ASEAN Integration, Manufacturing Industry, Competitiveness, Panel Data Analysis